Protein-spatiotemporal partition releasing gradient porous scaffolds and anti-inflammatory and antioxidant regulation remodel tissue engineered anisotropic meniscus - Bingbing Xu; Jing Ye; Bao-Shi Fan; Xinjie Wang; Ji-Ying Zhang; Shitang Song; Yifan Song; Wen-Bo Jiang; Xing Wang; Jia-Kuo Yu (Bioactive Materials, 2023)
Meniscus is a wedge-shaped fibrocartilaginous tissue, playing important roles in maintaining joint stability and function. Meniscus injuries are difficult to heal and frequently progress into structural breakdown, which then leads to osteoarthritis. Regeneration of heterogeneous tissue engineering meniscus (TEM) continues to be a scientific and translational challenge. The morphology, tissue architecture, mechanical strength, and functional applications of the cultivated TEMs have not been able to meet clinical needs, which may due to the negligent attention on the importance of microenvironment in vitro and in vivo. Herein, we combined the 3D (three-dimensional)-printed gradient porous scaffolds, spatiotemporal partition release of growth factors, and anti-inflammatory and anti-oxidant microenvironment regulation of Ac2-26 peptide to prepare a versatile meniscus composite scaffold with heterogeneous bionic structures, excellent biomechanical properties and anti-inflammatory and anti-oxidant effects. By observing the results of cell activity and differentiation, and biomechanics under anti-inflammatory and anti-oxidant microenvironments in vitro, we explored the effects of anti-inflammatory and anti-oxidant microenvironments on construction of regional and functional heterogeneous TEM via the growth process regulation, with a view to cultivating a high-quality of TEM from bench to bedside.